Konsep Akuntabilitas dalam Gereja Katolik - Leonita Catherine Wijaya; Whedy Prasetyo; Alwan Sri Kustono (Jurnal Ekonomi Akuntansi dan Manajemen, 2020)
This study aims to describe the concept of income and burden on the Holy Heart of the Virgin Mary Catholic Church. This research chooses the Sacred Heart of the Virgin Mary Catholic Church as the object of research, because the Sacred Heart of the Virgin Mary is a newly established church, so that accountability is an important pillar for the newly established church to gain the trust of the people. This research uses the interpretivis paradigm by using the case study method in its research method. Thus, primary and secondary data sources are needed in research, and use interviews, observations and documentation in this study. Data analysis methods used are data collection, data reduction, data presentation, and verification as well as drawing conclusions. The results of this study indicate that in general the Sacred Heart Church of the Virgin Mary has carried out finansial management properly, where finansial management is carried out accordingly, starting from planning to accountability. In this church the proposal is made in issuing funds used for ecclesiastical activities. The finansial reporting system made by finansial managers is fairly simple because tis based on trust in managing finances obtained through collectives and contributions from the people to fulfill the operational activities of the church. Keywords: Accountability, Transparency, Church, Accounting